اﺛﺮ طﺮﯾﻘﺔ ﺣﻞ اﻟﻤﺸﻜﻼت ﻓﻲ ﺗﺤﺼﯿﻞ ﻗﻮاﻋﺪ اﻟﻠﻐﺔ اﻟﻜﺮدﯾﺔ ﻟﺪى طﺎﻟﺒﺎت اﻟﺼﻒ اﻟﺮاﺑﻊ اﻟﻌﻠﻤﻲ (Journal of the College of Education for Women, 2019)
This research aims at identifying the effect of problem solving strategy on the achievement of Kurdish language grammer of femal students at the fourth preperatory school. To achieve the study aims , the researcher has chosen intentionally this sample to apply the experiement . The study sample cosists 0f (58) female students distributed randomly on two groups. The experiemental group is taught according to problem- solving strategy and it is (29) female students, while the control group which is also (29) individuals is taught according to the traditional way of teaching . The two groups have been matched statistically in term of age , the academic achievement for the father and mother , intelligence, and the linguistic ability. The experiement lasted one semester. The researcher has constructed an achievement test composed of (30) multiple choice, completion, and matching items. Test reliabitiy has been ascertained to be (0,83) by applying pearson correlation formula and the T- test . statistical results have shown that there is a stastically significant difference to the experiemental group which has been taught according to the problem – solving strategy researcher has come up with many recommendations to improre teachers of Kurdish performances and show them the most modern methods of Teaching .